The relationship of small vessel disease burden on cerebral and regional brain atrophy rates and cognitive performance over one year of follow-up after transient ischemic attack - Reaume, Noaah; Reid, Meaghan; Tadros, George S.; Chacinski, Dorothy; Denroche, Britney; Aftab, Arooj; Wu, Pauline; Gupta Sah, Rani; Wang, Meng; Smith, Eric E.; Frayne, Richard; Coutts, Shelagh B.; et al. (Frontiers in Neurology, 2023)
Background: Stroke, even when minor, increases the risk of dementia. We aimed to determine whether patients with transient ischaemic attack (TIA) exhibit higher rates of cerebral and regional atrophy 1-year after first stroke symptoms and evaluate the relationship with small vessel disease and cognitive performance.Methods: TIA patients and controls without cognitive symptoms underwent high-resolution T1weighted MRI and cognitive testing at baseline and 1-year. Percent brain volume change (PBVC) was measured, and the location of regional atrophy and small vessel disease (CSVD) burden was evaluated. Neuropsychological testing assessed memory, processing speed, and executive function.Results: A total of 76 TIA patients and 53 controls of mean age 67 (SD=8) and 68 years (SD=8) were recruited. TIA patients demonstrated greater improvement of visual memory and executive function at 1-year. TIA patients had greater median PBVC/year compared to controls (-0.79% [(-1.22)-(-0.38)] vs. -0.41% [(-0.62)-0.19]; p<0.001), and higher rates of volume loss (ml/year) in subcortical grey (-0.53 [